Review of the role of pyroptosis in benign prostatic hyperplasia in old males - CHEN Zixuan; LI Dong; LIU Min (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Pyroptosis, a new mode of programmed cell death, is primarily characterized by persistent cellular swelling that culminates in cell rupture. This process results in the release of large amounts of inflammatory factors, subsequently triggering an inflammatory response. Benign prostatic hyperplasia (BPH) is the most frequent urological disease in old males and is closely associated with changes in hormones and inflammation response. In recent years, the role of pyroptosis in the occurrence and development of BPH has also received increasing attention. This article summarizes the mechanisms of pyroptosis, concludes the pathogenesis associated with BPH in old males, and outlines the role of pyroptosis in BPH, to provide new ideas for finding more effective therapeutic measures for BPH through pyroptosis.